Performance analysis of InSb based QWFET for ultra high speed applications. (1st January 2015) - Subash, T. D.; Gnanasekaran, T.; Divya, C.
Abstract An indium antimonide based QWFET (quantum well field effect transistor) with the gate length down to 50 nm has been designed and investigated for the first time for L-band radar applications at 230 GHz. QWFETs are designed at the high performance node of the International Technology Road Map for Semiconductors (ITRS) requirements of drive current (Semiconductor Industry Association 2010). The performance of the device is investigated using the SYNOPSYS CAD (TCAD) software. InSb based QWFET could be a promising device technology for very low power and ultra-high speed performance with 5–10 times low DC power dissipation.